Channeled coolant plate: a new method to enhance freshwater production from an air gap membrane distillation (AGMD) desalination unit - Bahar, Rubina; Hawlader, Mohammad Nurul Alam; Mohamed Ariff, Tasnim Firdaus (Elsevier, 2015)
Air gap membrane distillation (AGMD) desalination process incorporates phase change and transport of vapor from saline water through a hydrophobic membrane and an air gap due to difference in vapor pressure across the membrane and a coolant plate. In this study, an attempt was made to observe the effect of a channeled coolant plate instead of a flat plate for distillation of saline water. Since the AGMD process has limited distillate production due to the resistance offered by the air gap, a specially designed coolant plate was used to manipulate the mass transfer by enhancing the heat transfer during condensation. For the same equivalent air gap, the freshwater production enhanced maximum up to 50% compared to a flat coolant plate for a coolant temperature of 25 °C. A one dimensional heat transfer model is developed and validated using the experimental data. The results obtained from the model matched well with experiments and it was used to predict freshwater production from various designs of finned coolant plates.